THE EFFECT OF OXYTOCIN MASSAGE ON THE PRODUCTION OF ASI OF BREASTFEEDING MOTHER IN THE WORKING AREA OF BANDA SAKTI PUBLIC HEALTH CENTER, BANDA SAKTI DISTRICT, LHOKSEUMAWE CITY, 2019 - Dahliana, Dahliana; Juwita, Zeva (Jukema (Jurnal Kesehatan Masyarakat Aceh), 2021)
Background: Massage or stimulation of the spine, neurotransmitters will stimulate the medulla oblongata to directly send messages to the hypothalamus in the hypophyseposteriorly to release oxytocin, causing the breasts to release milk. The purpose of this study was to determine the effect of oxytocin massage on milk production in breastfeeding mothers in the Banda Sakti Public Health Center, Banda Sakti District, Lhokeseumawe City. Metods: The study design was an analytical study using a cross sectional approach. The population in this study were all breastfeeding mothers who were in the Banda Sakti Public Health Center Lhokseumawe totaling 40 breastfeeding mothers. The sampling method in this study is to use the total population. Where the sample of this research is the entire population, amounting to 40 respondents. The trials in this study were conducted in Hagu Teungoh Village, Banda Sakti District, Lhokseumawe City with a total of 10 respondents, 30 questions with a product moment r value of 0,70. Result: The results showed that of the 28 breastfeeding mothers who did oxytocin massage, the majority of their milk production was smooth, namely 17 people (60,7%), while of the 12 breastfeeding mothers who did not oxytocin massage the majority of their milk production was not smooth, namely 9 people (75%). Recommendation: It is hoped that it can increase respondents knowledge in an effort to increase milk production and can inform the impact of the failure of the breastfeeding process.